Bureau Of Mines Mineral Investigations In The Juneau Mining District, Alaska, 1984-1988 - Volume 2.- Detailed Mine, Prospect, And Mineral Occurrence Descriptions - Section A - Haines-Klukwan-Porcupine Subarea ? Introduction - Jan C. Still (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The Haines-Klukwan-Porcupine subarea of the Juneau Mining District (JMD) is located in the northern portion of the JMD and consists of the land between the Alaska-British Columbia boundary, the Chilkoot Valley, Glacier Bay National Park boundary, and extending south to the Davidson Glacier and the Chilkat Peninsula and Islands (fig A-I). This area was studied as part of the larger JMD study in a cooperative effort between the Alaska Division of Geological and Geophysical Surveys (ADGGS) and the Bureau during 1985 to 1988. Prior to this, during 1984, the ADGGS and the Bureau cooperated in a study of the Porcupine mining area and during 1981 to 1983 conducted separate studies in the area. Field work was conducted by foot, boat, truck, and helicopter. Figure A-I shows the Haines-Klukwan-Porcupine sub-area and shows the areas covered by previous Bureau and ADGGS studies. PHYSIOGRAPHY AND CLIMATE The physiography of the subarea ranges from gentle to rugged. Glaciers formed the major features in the sub-area and left "U" shaped steep walled valleys and rugged mountains. The Chilkat, Chilkoot, Klehini, Tsirku, and Takhin are the major rivers in the subarea. The higher mountains are glacier clad and some valleys still harbor glaciers that reach the valley floors. Lush forests and dense brush predominate up to timberline at about the 2,000-foot elevation. Low point in the subarea is at sea level in the area around Haines while the high point is 7,434 feet at: Mount Henry Clay in the Porcupine mining area.